2018
DOI: 10.1002/med.21499
|View full text |Cite
|
Sign up to set email alerts
|

Activity and selectivity cliffs for DPP‐IV inhibitors: Lessons we can learn from SAR studies and their application to virtual screening

Abstract: The inhibition of dipeptidyl peptidase-IV (DPP-IV) has emerged over the last decade as one of the most effective treatments for type 2 diabetes mellitus, and consequently (a) 11 DPP-IV inhibitors have been on the market since 2006 (three in 2015), and (b) 74 noncovalent complexes involving human DPP-IV and drug-like inhibitors are available at the Protein Data Bank (PDB). The present review aims to (a) explain the most important activity cliffs for DPP-IV noncovalent inhibition according to the binding site st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 203 publications
(688 reference statements)
1
41
0
Order By: Relevance
“…Molecular docking showed that Ile-Pro-Ile and its associated peptide analogs established similar interactions with the active site of porcine DPP-IV (Figure 6 ). These interactions are consistent with those (i.e., with Glu205, Glu206, Tyr662) that have been demonstrated earlier with the S 1 pocket of the active site of DPP-IV ( 40 ). Nevertheless, there was no correlation between the computed scores and the experimentally determined DPP-IV IC 50 values (Figure 6 ; Table 2 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Molecular docking showed that Ile-Pro-Ile and its associated peptide analogs established similar interactions with the active site of porcine DPP-IV (Figure 6 ). These interactions are consistent with those (i.e., with Glu205, Glu206, Tyr662) that have been demonstrated earlier with the S 1 pocket of the active site of DPP-IV ( 40 ). Nevertheless, there was no correlation between the computed scores and the experimentally determined DPP-IV IC 50 values (Figure 6 ; Table 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Several structural and physicochemical parameters of molecules have been shown to affect their ability to inhibit DPP-IV ( 40 ). The hydrophobicity of amino acids located within specific positions of peptides is thought to be of importance for the inhibition of DPP-IV ( 9 , 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than hydrophobicity, aromatic amino acid residues of peptides are important to inhibit DPP-IV. A previous study [ 33 ] suggested that the potency of DPP-IV inhibitors is related to the presence of aromatic rings as they form hydrophobic interactions with the DPP-IV catalytic domain. More recently, it has confirmed the importance of the presence of hydrophobic residues and a proline at the first, second, third, or fourth Nt position of peptides displaying potent DPP-IV inhibitory properties [ 13 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to a recent review about DPP4 inhibitors, Glu205, Glu206, and Tyr662 in DPP4 are believed to be the most import anchor points helping inhibitors recognize DPP IV. Since we used different protein with (Ojeda-Montes et al, 2018), for the convenience of comparison, we performed sequence alignment and renumbered all residues so that the residue number we used could match (Ojeda-Montes et al, 2018). In Figure 10 , it can be seen that DeepScore also favored these three residues and gave them fairly high scores.…”
Section: Resultsmentioning
confidence: 99%